Measurement of thermophysical property of plasma forming tungsten nanofiber layer. (12th April 2016) - Kajita, Shin; Yagi, Takashi; Kobayashi, Kenichi; Tokitani, Masayuki; Ohno, Noriyasu
Abstract: Thermophysical property of a nanostructured tungsten layer formed on a tungsten film was investigated. A 1-µm-thick tungsten film deposited on a quartz glass substrate was irradiated with a high density helium plasma at the surface temperature of 1500 K. The plasma irradiation led to the formation of highly porous fiberform-nanostructured tungsten layer with a thickness of 3.5 µm. Impulse heating was applied at the interface of the film/substrate, and transient heat diffusion was observed using a pulsed light heating thermoreflectance apparatus. The thermoreflectance signals clearly differed between the nanostructure existing and mechanically removed regions; the difference can be attributed to thermal effusivity of the nanostructured tungsten layer. The estimated thermal conductivity of the nanostructured tungsten decreases to ∼2% of that of bulk when the density of the nanostructure is assumed to be ∼6% of the bulk value.